The girl in the lake - Brown, India Hill, 1991- (Scholastic Press, 2022)
Celeste is not looking forward to spending two weeks at her grandparents' lake house with her brother, Owen, and their cousins Capri and Daisy. Celeste has never been comfortable around water and she's just failed her swim test, so the lake has no appeal to her. But not long after they arrive, strange things start happening, and Celeste starts to see a ghostly girl everywhere she looks. She thinks she's imagining things, but she begins to wonder what could the girl want if she is real.